Why the International Criminal Court Cannot Afford Justice for the Crime of Aggression Against Ukraine and what is the Way Forward? - Zolotar, Anna; Murachov, Vladyslav (Vilnius University Open Series, 2024)
The article focuses on the investigation at the International Criminal Court for the crime of aggression committed by Russia and the limitations that exist for ensuring justice at the ICC, and analyzes alternatives for punishing those responsible for aggression against Ukraine.